1998
DOI: 10.1088/0953-4075/31/7/003
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative recombination of isotopes with an ultra-cold electron beam from a superconducting electron cooler in a storage ring

Abstract: The dissociative recombinations of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 16 publications
4
38
0
Order By: Relevance
“…8. Our rapidly oscillating results full of dense resonance regions are convolved over the electron beam energy spreads of ∆E || = 0.1 meV and ∆E ⊥ = 10 meV, estimated in the previous experiments [7,9]. Evidently the difference between the two theoretical approaches is quite small at lower energies (below 100 meV) and it almost disappears at the collision energies above 100 meV.…”
Section: Dissociative Recombinationmentioning
confidence: 97%
See 1 more Smart Citation
“…8. Our rapidly oscillating results full of dense resonance regions are convolved over the electron beam energy spreads of ∆E || = 0.1 meV and ∆E ⊥ = 10 meV, estimated in the previous experiments [7,9]. Evidently the difference between the two theoretical approaches is quite small at lower energies (below 100 meV) and it almost disappears at the collision energies above 100 meV.…”
Section: Dissociative Recombinationmentioning
confidence: 97%
“…Furthermore, the relative simplicity of the system helps to gauge new experimental setups while also serving as a benchmark for different theoretical models. For these reasons, the low-energy collision process between electrons and the HeH + cations has attracted experimental interest [2][3][4][5][6][7][8][9] and theoretical studies [3,[10][11][12][13][14][15] over the past three decades.…”
Section: Introductionmentioning
confidence: 99%
“…The rotational constants for the lowest vibrational levels of HeH + are in the interval 20-33 cm −1 (see Table 1). The energy resolution of existing experimental data on e − + HeH + collisions is much worse [9]. Detailed rotational state-to-state thermally-averaged rate coefficients for rotational transitions without changing the vibrational state might be useful to model very cold environment, below 40 K. Due to this reason the rate coefficients obtained in the present study should not be viewed as accurate below 40 K. Theoretical rate coefficients for rotational excitation at low temperatures will be presented in a separate study.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…One of the most important processes is the dissociative recombination. Cross sections for this process were measured and calculated in several previous studies [8][9][10][11][12][13]. Another process, relevant for the ISM [14] and fusion reactors, in the vibrational excitation and (de)-excitation,…”
Section: Introductionmentioning
confidence: 99%
“…HeH + and NeH + do not have curve crossings [1,3] between the ion ground state and a repulsive neutral state that would lead to a strong direct recombination process (see figure 1). While it was originally believed that HeH + would exhibit a very small recombination rate [4], experimental studies using the merged beams method both in a single pass [5,6] and multi-pass mode [7,8] have revealed that in fact at low collision energies the measured recombination cross section is quite large and has a highly resonant structure. This observation has received support from theoretical studies [9,12].…”
Section: Introductionmentioning
confidence: 99%